The microbial conductor of cancer hallmarks: intratumoral microbiome as a multidimensional oncogenic modulator - Wu, Yibin; Zhou, Mengyan; Wan, Yiqi; Wei, Ke; Ma, Shucheng; Cheng, Lijuan; Lin, Ting; He, Lan; He, Yingchun; Zhou, Fangliang (Frontiers in Microbiology, 2026)
The intratumoral microbiome, comprising diverse bacteria, fungi, and viruses residing within tumor tissues, is increasingly recognized as a multidimensional oncogenic modulator, acting akin to a “microbial conductor” orchestrating key cancer hallmarks. Its compositon exhibits substantial heterogeneity across individuals and is closely associated with the host immunity, the tumor microenvironment (TME), and therapeutic efficacy. Specific microbial species can “conduct” pro-tumorigenic processes by producing carcinogenic metabolites, dysregulating inflammatory signaling, or facilitating immune evasion. Conversely, other microorganisms may exert anti-tumorigenic effects by stimulating anti-tumor immunity or directly inhibiting cancer cell proliferation. Furthermore, the intratumoral microbiome can influence therapeutic outcomes by modulating the metabolism of chemotherapeutic agents or altering the efficacy of immunotherapies. Therefore, a deeper understanding of the intratumoral microbiome and its complex interplay with tumors holds immense potential to unravel fundamental mechanisms of cancer development and progression, while simultaneously revealing novel avenues for precision oncology strategies. This review outlines the biological roles of the microbiota in modulating the hallmarks of cancer hallmarks, summarizes current knowledge on its multidimensional interactions driving tumor progression, and discusses the translational potential of targeting or leveraging the intratumoral microbiome based on recent advancements. Future research integrating multi-omics profiling, spatial technologies, and functional validation will be essential for resolving methodological limitations and accelerating the clinical translation of microbiome-based interventions.